Preventive strategies and potential therapeutic interventions for delirium in sepsis. Issue 4 (7th August 2016) - Souza-Dantas, Vicente Cés; Póvoa, Pedro; Bozza, Fernando; Soares, Marcio; Salluh, Jorge
ABSTRACT: Delirium is the most frequent and severe clinical presentation of brain dysfunction in critically ill septic patients with an incidence ranging from 9% to 71%. Delirium represents a significant burden for patients and relatives, as well as to the health care system, resulting in higher costs, long-term cognitive impairment and significant risk of death after 6 months. Current interventions for the prevention of delirium typically involve early recognition and amelioration of modifiable risk factors and treatment of underlying conditions that predisposes the individual to delirium. Several pharmacological interventions to prevent and treat delirium have been tested, although their effectiveness remains uncertain, especially in larger and more homogeneous subgroups of ICU patients, like in patients with sepsis. To date, there is inconsistent and conflicting data regarding the efficacy of any particular pharmacological agent, thus substantial attention has been paid to non-pharmacological interventions and preventive strategies should be applied to every patient admitted in the ICU. Future trials should be designed to evaluate the impact of these pharmacologic interventions on the prevention and treatment of delirium on clinically relevant outcomes such as length of stay, hospital mortality and long-term cognitive function. The role of specific medications like statins in delirium prevention is also yet to be evaluated.